Inhibition of key enzymes related to diabetes and hypertension by Eugenol in vitro and in alloxan-induced diabetic rats. (25th July 2013) - Mnafgui, Kais; Kaanich, Fatima; Derbali, Amal; Hamden, Khaled; Derbali, Fatma; Slama, Sadok; Allouche, Noureddine; Elfeki, Abdelfattah
Abstract: The present study investigated the effect of treating diabetic rats with eugenol (EG). In vitro enzyme activity was measured in the presence of eugenol, and it was found to inhibit pancreatic α-amylase (IC50  = 62.53 µg/mL) and lipase (IC50  = 72.34 µg/mL) as well as angiotensin converting enzyme (ACE) activity (IC50  = 130.67 µg/mL). In vivo, EG reduced the activity of amylase in serum, pancreas and intestine also the peak level of glucose by 60% compared to diabetic rats. Furthermore, eugenol similar to acarbose reduced serum glycosylated hemoglobin (HbA1c), lipase and ACE levels. In addition, treatments with EG showed notable decrease in serum total-cholesterol, triglycerides and low density lipoprotein-cholesterol levels with an increase of high density lipoprotein-cholesterol. Overall, EG significantly reverted back to near normal the values of the biochemical biomarkers such as transaminases (AST&ALT), alkaline phosphatase (ALP), creatine phosphokinase (CPK) and gamma-glutamyl transpeptidase (GGT) activities, total-bilirubin, creatinine, urea and uric acid rates.